The bodyguard [videorecording (DVD)] - Jackson, Mick; Costner, Kevin; Costner, Kevin; Houston, Whitney; Kemp, Gary, 1959-; Waite, Ralph, 1928-2014 (Warner Home Video, 2005)
In her film debut, Houston plays Rachel Marron, a music/movie superstar at her peak. Fans want to see her, hear her, touch her. But one wants to kill her - and that's where security expert Frank Farmer (Costner) comes in. Farmer is a professional who never lets his guard down. Rachel's glamorous life often puts her at risk. Each expects to be in charge. What they don't expect is to fall in love.